2005
DOI: 10.1042/cs20050026
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal administration induces diabetes-like microvascular changes and perturbs the healing process of cutaneous wounds

Abstract: Increased formation of MG (methylglyoxal) and related protein glycation in diabetes has been linked to the development of diabetic vascular complications. Diabetes is also associated with impaired wound healing. In the present study, we investigated if prolonged exposure of rats to MG (50-75 mg/kg of body weight) induced impairment of wound healing and diabetes-like vascular damage. MG treatment arrested growth, increased serum creatinine, induced hypercholesterolaemia (all P < 0.05) and impaired vasodilation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(123 citation statements)
references
References 45 publications
(42 reference statements)
7
108
0
1
Order By: Relevance
“…Previous studies have shown that diets high in MG-derived AGEs (and therefore, presumably, MG) are able to induce vascular inflammation and atherogenesis in diabetic apoE KO mice (37), but control mice were unaffected. Other studies have suggested that MG may be a pathogenic factor for the development of endothelial dysfunction (38), renal damage (39), insulin resistance (40), and macrophage activation (41), all of which may have contributed to atherogenesis in our model. It has also been reported that exposure to MG may be associated with the development of dyslipidemia (40) and/or hypertension (38).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies have shown that diets high in MG-derived AGEs (and therefore, presumably, MG) are able to induce vascular inflammation and atherogenesis in diabetic apoE KO mice (37), but control mice were unaffected. Other studies have suggested that MG may be a pathogenic factor for the development of endothelial dysfunction (38), renal damage (39), insulin resistance (40), and macrophage activation (41), all of which may have contributed to atherogenesis in our model. It has also been reported that exposure to MG may be associated with the development of dyslipidemia (40) and/or hypertension (38).…”
Section: Discussionmentioning
confidence: 90%
“…Other studies have suggested that MG may be a pathogenic factor for the development of endothelial dysfunction (38), renal damage (39), insulin resistance (40), and macrophage activation (41), all of which may have contributed to atherogenesis in our model. It has also been reported that exposure to MG may be associated with the development of dyslipidemia (40) and/or hypertension (38). In our studies, neither MG administration nor BBGC modified lipid or blood pressure levels, although our mice had marked dyslipidemia due to genetic deletion of the apoE gene, a model in which diabetes itself has only modest effects on already elevated lipid levels (Table 1).…”
Section: Discussionmentioning
confidence: 90%
“…Prospective Diabetes Study [3] strongly suggest the importance of hyperglycemia in the pathogenesis of chronic complications of diabetes mellitus including diabetic renal disease. Hyperglycemia leads to diabetic nephropathy (DN) via multiple mechanisms, and among them increased aldose reductase (AR) activity [4,5], nonenzymatic glycation and glycooxidation [6,7], activation of protein kinase C (PKC) and hexosamine pathway [8][9][10], arachidonic acid metabolism via 12/15-lipoxygenase pathway [11,12], and triose phosphate accumulation [13] are the best studied. Growing evidence obtained in diabetic animals (primarily, STZ (streptozotocin)-diabetic rats and mice) [14][15][16][17] as well as cell culture models [18][19][20] implicates free radicals and the potent oxidant peroxynitrite (a product of superoxide anion radical reaction with nitric oxide) in both hemodynamic and metabolic abnormalities leading to DN.…”
Section: Introductionmentioning
confidence: 99%
“…Methylglyoxal reacts with cysteine, lysine and arginine residues on proteins to form advanced glycation end-products (AGEs) that affect protein function (5,6). Administration of MG to mice, rats, or cells in culture, results in physiological changes observed in diabetic patients such as collagen accumulation in kidneys, hypercholesterolemia, microvasculature degeneration, and insulin resistance (7)(8)(9).…”
mentioning
confidence: 99%